(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Introduction: Systematic reviews report that CHWs in low-income countries have demonstrated the capacity to improve antenatal, perinatal and post-partum service utilization and to prevent perinatal and maternal deaths by early recognition and referral of complicated pregnancies. Due to these successes and the increasing recognition of the crisis in human resources for health, deployments of CHWs have become a popular strategy to delivery primary health care at the community level. In India Many Programme run at grass root level with deployment of peripheral health workers male & female. One such programme is Village Health & Nutrition Day. Objective: Thus current study attempted to identify if there is any gap or problems in delivery of the services. Method: A community based Cross Sectional study was conducted for a Period 1 year. One PHC was selected by Simple Random Sampling by lottery method, from each of the 7 blocks of study district. One Mamta day of all the Sub Centres of each of the selected 7 PHCs was evaluated. Selected 7 PHCs have total 40 sub centres, so total 40 FHW were Interviewed. It included quantitative as well as qualitative methodology. Results: Most common site was Anganwadi. Insufficient logistics was the key problem. Other problems were lack of community participation, no perceived concept of preventive health, psychosocial barriers. Suggestions given by FHWs were reduction in work load with proper distribution & timely receipt of grant. Conclusion: Interval evaluation of FHWs helps in identification & problem solving strategies for an outreach programme.